User Satisfaction With Telehealth: Study of Patients, Providers, and Coordinators. Issue 4 (October 2015) - Unknown
Abstract : The aim of this study was to examine the satisfaction with telehealth technologies of all users—patients, health care providers, and telehealth presenters. As the use of videoconferencing in health care is rapidly increasing to allow adequate and timely access to care for patients from rural areas, it is important to examine how these technologies are perceived and utilized. Three separate surveys were used to collect data: patient, provider, and telehealth coordinator. Patient surveys were collected in a paper format, while provider and coordinator surveys were done using REDCap (Research Electronic Data Capture) application. Findings indicate high satisfaction with telehealth, as well as confidence in providing care via distance. While this is encouraging for both patients and health care organizations, further studies should be done to include urban telehealth as well as other types of health care organizations utilizing videoconferencing for clinical appointments.